THE HISTORICAL DYNAMICS OF THE JAMBI SULTANATE AND ITS CONTRIBUTION TO THE DEVELOPMENT OF ISLAM IN JAMBI IN THE XIX CENTURY - Abdul Halim; Anis Malik Thoha (PT. Jurnal Center Indonesia Publisher, 2026)
This study examines the reconstruction of the history of the Sultanate of Jambi and its role in the development of Islam in Jambi in the 19th century. This study highlights the process of integration between Malay customs and Islamic sharia in the government, law, and social life systems of the community. Through a historical approach and analysis of manuscripts, colonial archives, and customary manuscripts, this research explains that the Sultanate of Jambi developed as a Malay-Muslim kingdom that made the principle of Adat Bersendi Syarak, Syarak Bersendi Kitabullah (ABS-SBK) as the basis of political and social legitimacy. The results of the research show that the relationship between customs and Islam in the Sultanate of Jambi is integrative and dynamic, especially in the field of siyasah and jinayat. Islam not only functioned as a religious identity, but also as a source of legitimacy for power and a socio-political instrument in the face of Dutch colonialism. The Sultanate of Jambi also played an important role in defending the Malay-Islamic identity and forming a customary government system that influenced the development of the Jambi society until the contemporary period.